PERSISTENCE OF BLOOD PRESSURE PHENOTYPES ACCORDING TO OFFICE AND 24 HOUR AMBULATORY BLOOD PRESSURE IN CHILDREN. (June 2022) - Martinez, Fernando; Alvarez, Julio; Ponce, Francisco; Redon, Josep; Lurbe, Empar
Abstract : Objective: To assess the persistence of BP phenotypes according to office and 24-h ABPM in youth over time. Design and method: Retrospective study including 582 children who underwent measurement of both office BP (OBP) and ABPM on the same day. The second office BP and ABPM was performed within 1 year apart. OBP was measured using an oscillometric device validated in children. ABPM was performed using oscillometric SpaceLabs 90207 monitors. OBP and ABPM were classified according to the criteria of the ESH (Lurbe et al J Hypertens 2016). Four phenotypes based on OBP and ABPM were defined: true normotensives, sustained hypertensives, white-coat hypertensives, and masked hypertensives. Persistence and Kappa statistic were used to evaluate the concordance of BP phenotypes. Factors related with persistence on BP phenotypes were evaluated using logistic regression models. Results: At the initial assessment, the majority of children fell within the category of true normotension (77%), followed by masked hypertension (13%), sustained hypertension (5%) and white coat hypertension (5%). The prevalence of true normotensive increased significantly in the follow-up. The flow through phenotypes is shown in the Figure. Only 38 initial true normotensive patients changed to other categories, mainly masked (12); 63 of initial masked hypertension changed, mainly to normotensive (58); 24 of white coat changed predominantly to normotension (16); finally, 25 of sustained changed, largely to normotension (14), but 9 children migrated to masked. The overall agreement was 74.2% (kappa 0.20). The grade of agreement was slightly higher for boys than for girls. In the multivariable model, higher age showed to be a protective factor, whereas increased office SBP and waist circumference were significant risk factors. The masked hypertensive phenotype carried the highest risk for lack of persistence. Conclusions: Children with hypertensive BP phenotypes should be re-evaluated because a large percentage of them will become normotensive. High BP levels and high BMI z-score or waist circumference were significant risk predictors for the lack of persistence on BP phenotypes.